On the earliest English translation of the "Laws of Oléron" and its editions - Lis, Kinga (My University, 2020)
The Laws of Oléron are a compilation of regulations binding in north-western Europe. They concern relationships on board a ship and in ports, as well as between members of one crew and those of another when it comes to safe journey. Even though the “code” was known in England at the beginning of the 14th century, it was only in the 16th century that it was translated from French into (Early Modern) English. The literature on the topic mentions two independent 16th-century renditions of the originally French text (Lois d’Oléron) but disagrees as to the authorship of the earliest translation, its date and place of creation, the mutual relationship between the two, their content and respective source texts. Strikingly, three names appear in this context: Thomas Petyt, Robert Copland, and W. Copland. The picture emerging from various accounts concerning the translations is very confusing. It is the purpose of this paper to trace the history of the misconceptions surrounding the Early Modern English versions of the Laws of Oléron, and to illustrate how, by approaching them from a broader perspective, two hundred years of confusion can be resolved. The wider context adopted in this study is that of a book as a whole, and not of an individual text within the book, set against the backdrop of the printing milieu. The investigation begins with a brief inquiry into the lives and careers of the three people named with respect to the two renditions, in an attempt to determine whether these provide any grounds for disagreement. The analysis also juxtaposes the relevant renditions as far as their contents, layout, and the actual texts are concerned in order to establish what the relationship between them is and whether it could account for the confusion surrounding the translations.
Keywords: Laws of Oléron; The Rutter of the Sea; Thomas Petyt; Robert Copland; Pierre Garcie; edition; 16th-century English printers